Critical Editing and Philological Analysis of the First Chapters of Trito-Isaiah (Isa 56–57) Based on the Coptic Manuscript sa 52 (M 568) and Other Coptic Manuscripts in the Sahidic Dialect and the Greek Text of the Septuagint - Bąk, Tomasz Bartłomiej (The Biblical Annals, 2026)
This article presents a critical edition and philological analysis of the first two chapters of Trito-Isaiah (Isa 56–57), drawing primarily on the Coptic manuscript sa 52.2 alongside other extant manuscripts in the Sahidic dialect. The initial section provides an overview of the relevant portion of codex sa 52 (M 568) containing the text under study, followed by a concise list and description of additional manuscripts that preserve at least some verses from Isa 56–57. The core of the article features the Coptic text in the Sahidic dialect, accompanied by an English translation. A tabular comparison highlights deviations between the Sahidic text and the Greek Septuagint, its source, including additions, omissions, lexical variations, and semantic shifts in the Coptic translation. The final section addresses complex philological challenges, whether inherent to the Coptic text or arising from its relationship to the Septuagint, aiming to resolve interpretive difficulties.